2008
DOI: 10.1016/j.idairyj.2007.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, biochemical and biogenic amine profiles of Terrincho cheese manufactured in several dairy farms

Abstract: Terrincho is a Portuguese traditional cheese, bearing a protected denomination of origin (PDO) status, which is manufactured from raw ewes' milk and ripened for a minimum period of 30 d. The objectives of this research effort were to characterize the microbiological and biochemical profiles of this cheese, manufactured in several dairy farms during the winter cheesemaking season (December through March), and establish tentative correlations between these profiles and formation of biogenic amines. For this goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 25 publications
5
49
1
4
Order By: Relevance
“…However, it was reported that e. faecalis produced 2-phenylethylamine and also substantial amounts of tyramine in skim milk, which is the main raw material of fermented dairy products (O'Brien et al 2004). Significant part of Terrincho sheep cheese microflora form enterococci, they contribute to the increased production of tyramine, cadaverine, putrescine and other BA according to the amount of free amino acids (Pintado et al 2008). enterococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was reported that e. faecalis produced 2-phenylethylamine and also substantial amounts of tyramine in skim milk, which is the main raw material of fermented dairy products (O'Brien et al 2004). Significant part of Terrincho sheep cheese microflora form enterococci, they contribute to the increased production of tyramine, cadaverine, putrescine and other BA according to the amount of free amino acids (Pintado et al 2008). enterococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…We found that cadaverine was positively correlated with cell density of mesophilic lactococci. Pintado et al (2008) reported a positive correlation between lactococci and tyramine. Among mesophilic lactococci, some isolates belonging either to Lactococcus sp.…”
Section: Discussionmentioning
confidence: 98%
“…Na zależność między zawartością amin biogennych w serach i obecnością w nich niektó-rych gatunków drobnoustrojów wskazują wyniki badań wielu autorów (8,11,12,13,24,25,28 (3,8).…”
Section: Artykuł Przeglądowy Reviewunclassified